A review of thermal runaway prevention and mitigation strategies for lithium-ion batteries. (December 2022) - Shahid, Seham; Agelin-Chaab, Martin
Highlights: Thermal runaway characterization mechanisms are discussed. Models and predictions strategies related to thermal runaway are summarized. Thermal runaway prevention is explained. Thermal runaway is still a challenging problem in electric vehicle applications. Abstract: Lithium-ion batteries are widely considered the leading candidate energy source for powering electric vehicles due to their high energy and power densities. The thermal runaway of lithium-ion batteries is the phenomenon of chain exothermic reactions within the battery. These reactions cause a sharp rise in the internal battery temperature causing the inner structures of the battery to destabilize and degrade, which eventually leads to the failure of the battery. This paper provides a comprehensive review of the key aspects of the thermal runaway processes, which consists of thermal runaway initiation mechanisms, thermal runaway propagation, and the characterization of vented gases during the thermal runaway process. Thermal runaway is a major safety concern; therefore, the development of mathematical and numerical models to predict thermal runaway is reviewed, which provides useful data to design and develop battery packs with thermal runaway safety features. Furthermore, the development of effective battery thermal management systems is discussed, which is essential to prevent thermal runaway initiation. Finally, mitigation strategies are reviewed, which are developed to contain and minimize damages when thermal runaway occurs.